α-Amylase inhibitory property, antioxidant activity and toxicological study of Salvia chloroleuca - I. Salimikia; Monsef-Esfahani H.R; M. Sharifzadeh; A.R. Gohari; M. Salek (Iranian Society of Pharmacognosy, 2015)
Background and objectives: Salvia chloroleuca Rech. f. & Allen., is an endemic species growing wildly in north east and center parts of Iran but there is no information about its safety. To provide information about the safety of the species, we evaluated its acute and sub chronic toxicity in rats. Methods: In acute toxicity study, the aqueous methanol (80%) extract at a single dose of 2000 mg/kg/day was administered orally to male and female rats and signs of toxicity two weeks after administration were observed. For the subchronic toxicity test, the extract at doses of 250, 500 and 1000 mg/kg/day were orally administered to the rats of both sexes for 45 days. Mortality, clinical signs of toxicity and body weight changes were monitored during the study. Moreover, α-amylase enzyme inhibition, total phenol content, and antioxidant (DPPH and FRAP assays) activity of different fractions of aerial part were evaluated. Results: The methanol and aqueous methanol (80%) extracts showed α-amylase enzyme inhibition with IC50 values 14.03 mg/mL and 18.05 mg/mL, respectively. The IC50 value for ethyl acetate, methanol and aqueous methanol (80%) extracts in radical scavenging assay were calculated as 288.83, 97.93, and 108.02 μg/mL, respectively. Among all extracts, methanol (228.4±12.05) demonstrated the highest FRAP value, followed by methanol (80%) extract (220.4±8.08) and ethyl acetate extract (156.4±10.06). In acute toxicity and subchronic study, neither mortality nor changes in behavior or any other parameter were observed. Conclusion: Our findings indicate potent in vitro α-amylase and antioxidant activity of S. chloroleuca andpropose its potential as an anti-diabetic agent for treatment of noninsulin-dependent diabetes mellitus (NIDDM) patients.